A prospective study of grey matter and cognitive function alterations in chemotherapy-treated breast cancer patients - Lepage, Chris; Smith, Andra M; Moreau, Jeremy; Barlow-Krelina, Emily; Wallis, Nancy; Collins, Barbara; MacKenzie, Joyce; Scherling, Carole (Université d'Ottawa | University of Ottawa, 2014)
Abstract Purpose Subsequent to chemotherapy treatment, breast cancer patients often report a decline in cognitive functioning that can adversely impact many aspects of their lives. Evidence has mounted in recent years indicating that a portion of breast cancer survivors who have undergone chemotherapy display reduced performance on objective measures of cognitive functioning relative to comparison groups. Neurophysiological support for chemotherapy-related cognitive impairment has been accumulating due to an increase in neuroimaging studies in this field; however, longitudinal studies are limited and have not examined the relationship between structural grey matter alterations and neuropsychological performance. The aim of this study was to extend the cancer-cognition literature by investigating the association between grey matter attenuation and objectively measured cognitive functioning in chemotherapy-treated breast cancer patients. Methods Female breast cancer patients (n = 19) underwent magnetic resonance imaging after surgery but before commencing chemotherapy, one month following treatment, and one year after treatment completion. Individually matched controls (n = 19) underwent imaging at similar intervals. All participants underwent a comprehensive neuropsychological battery comprising four cognitive domains at these same time points. Longitudinal grey matter changes were investigated using voxel-based morphometry. Results One month following chemotherapy, patients had distributed grey matter volume reductions. One year after treatment, a partial recovery was observed with alterations persisting predominantly in frontal and temporal regions. This course was not observed in the healthy comparison group. Processing speed followed a similar trajectory within the patient group, with poorest scores obtained one month following treatment and some improvement evident one year post-treatment. Conclusion This study provides further credence to patient claims of altered cognitive functioning subsequent to chemotherapy treatment.